Permainan Gawang Ajaib untuk Meningkatkan Hasil Belajar Gerak Dasar Lempar Tangkap Siswa Sekolah Dasar - Arif Prabowo (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2018)
The research objective was to improve children’s movement, catching and throwing through wicket game during physical education. The subjects included twenty three six graders at the Public Elementary School 1 Losari in the academic year of 2016/2017. Data collection technique applied observation checklist. Data were analyzed descriptively and quantitatively. Research results show an improvement in the children’s basic movement, catching and throwing through magic wicket. The children’s improvement was evidenced in their learning outcomes. Prior learning, only five children (22%) achieved the minimum mastery level = 70. However, there are twenty one children (91%) achieved the minimum mastery level after learning.